How do personality characteristics of risky pregnant women affect their prenatal distress levels?: A Turkey university hospital cross-sectional study - Funda Evcili; Gulseren Daglar (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The prenatal distress level of the pregnant woman is influenced by many variables. Personality characteristics are one of the most important of these variables. Knowing personality characteristics of pregnant women contributes to the personalization of care. The purpose of this paper is to identify the effect of personality characteristics of pregnant women at risk on the prenatal distress level. Design/methodology/approach - A total of 438 women who were hospitalized based on a medical diagnosis associated with pregnancy were included in the study. The participants were administered the Personal Information Form, Cervantes Personality Scale and Revised Prenatal Distress Questionnaire. Data were evaluated using the SPSS 22.0 software program. Findings - Of the pregnant women, 27.4 percent found their ability to cope with stress insufficient, and one-fifth of them found their social support insufficient. The pregnant women at risk with introverted, neurotic and inconsistent personality were found to have high levels of prenatal distress. Research limitations/implications - This study was conducted on a group of Turkish pregnant women and cannot be generalized to other cultures. The data obtained from the research cannot be used to evaluate the psychological and physical disorders of the pregnant woman. Practical implications - All health care professionals should evaluate women not only physically but also mentally and emotionally, beginning with the preconceptional period. They should determine the conditions that create distress and identify the personality characteristics that prevent from coping with stress. By using cognitive and behavioral techniques, pregnant women should be trained to gain skills on subjects such as risk perception and stress management, personality characteristics and coping, problem solving, psychological endurance and optimism. Caring initiatives should be personalized in line with personality characteristics of pregnant women. The care offered within this framework will contribute to the strengthening and development of the health of not only the women but also the family and society, and to the reduction of health care costs. Social implications - Researchers have determined that pregnant women at risk with introverted, neurotic and inconsistent personality characteristics have higher distress levels. They have determined that these pregnant women find their ability to cope with stress more inadequate. It is vital to cope with stress during pregnancy due to its adverse effects on maternal/fetal/neonatal health. Originality/value - The prenatal distress level of the pregnant woman is influenced by many demographic (age, marital status and socioeconomic level), social (marital dissatisfaction, and lack of social support), personal (self-esteem, neuroticism and negative life experiences) and pregnancy-related (experiencing risky pregnancy, and previous pregnancy experiences) variables. Personality characteristics are one of the most important of these variables. This research is original because there are limited number of studies examining the effect of personality characteristics on prenatal distress level in the literature. And knowing the relationship between personality characteristics and distress by health professionals enables individualization of care. The care offered within this framework will contribute to the strengthening and development of the health of not only the women, but also the family and society, and to the decrease of health care costs.